Making Africa work a handbook for economic success - Mills, Greg. (London C. Hurst, 2017)
Over the next generation, Sub-Saharan Africa faces three big, inter-related challenges. Its population will double to 2 billion by 2045. By then, more than half of Africans will be living in cities. And this group of mostly young people will be connected with each other and the world through mobile devices. Properly planned for and harnessed, this situation is a tremendously positive force for change. But without economic growth and jobs, it could prove a political and social catastrophe. With these population increases, old systems of patronage and of muddling through will no longer work. Instead, if leaders want to remain in power, they will have to find a more dynamic means of promoting growth. A first-hand account of a rapidly changing region, Making Africa Work is a handbook for ensuring growth beyond commodities and creating jobs across the continent.
Includes bibliographical references (pages 271-303) and index.
Keywords: Economic development--Africa.